Use of eculizumab in children with allogeneic haematopoietic stem cell transplantation associated thrombotic microangiopathy - a multicentre retrospective PDWP and IEWP EBMT study - Svec, Peter; Elfeky, Reem; Galimard, Jacques-Emmanuel; Higham, Christine S; Dalissier, Arnaud; Quigg, Troy C; Bueno Sanchez, David; Han Lum, Su; Faraci, Maura; Cole, Theresa; Pichler, Herbert; Benítez-Carabante, Maria Isabel; et al. (Bone marrow transplantation, 2023)
Terminal complement blockade by humanised monoclonal antibody eculizumab has been used to treat transplantation-associated thrombotic microangiopathy (TA-TMA) in recent years. This retrospective international study conducted by the Paediatric Diseases (PDWP) and Inborn Error Working Party (IEWP) of the European Society for Blood and Marrow Transplantation (EBMT) describes outcome and response of 82 paediatric patients from 29 centres who developed TA-TMA and were treated with eculizumab between January 2014 and May 2019. The median time from hematopoietic stem cell transplantation (HSCT) to TA-TMA manifestation was 92 days (range: 7-606) and from TA-TMA diagnosis to the start of eculizumab treatment 6 days (range: 0-135). Most patients received eculizumab weekly (72%, n = 55) with a standard weight (kg)-based dose (78%, n = 64). Six months from beginning of eculizumab therapy, the cumulative incidence of TA-TMA resolution was 36.6% (95% CI: 26.2-47) and the overall survival (OS) was 47.1% (95% CI: 35.9-57.5). All 43 patients with unresolved TA-TMA died. The cause of death was HSCT-related in 41 patients. This study also documents poor outcome of patients without aGvHD and their frequent concomitant viral infections. Considering recent publications, intensified eculizumab dosing and complement monitoring could potentially improve upon outcomes observed in this study.
Keywords: dítě; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; lidé; retrospektivní studie; Thrombotic Microangiopathies; Antibodies, Monoclonal, Humanized; Humans; Retrospective Studies; Child; trombotické mikroangiopatie; humanizované monoklonální protilátky